The ets sequence is required for induction of erythroblastosis in chickens by avian retrovirus E26. - Nunn, M F (1989)
E26 is a replication-defective avian retrovirus that causes an erythroblastic leukemia in vivo and transforms hematopoietic precursor cells of both the erythroid and the myeloid lineages in vitro. The E26 genome contains two sets of cell-derived sequences, ets and myb. myb sequences are also present in avian myeloblastosis virus, which transforms myeloblasts exclusively. To determine whether the ets sequence is responsible for the erythroid specificity of E26, we analyzed the transforming activities of several viruses carrying mutations in the ets sequence constructed in vitro. The mutant viruses retained the ability to transform myeloid cells in vitro, indicating that the myb oncogene is sufficient for this viral function. However, the ets-deficient viruses did not cause an overt leukemia in chickens. The results indicate that the ets sequence is required for the induction of erythroblastosis by E26.